Workplace reform with changing management through the user participation workshop : the case study of Seiyo City Office / Ikumi Egawa - Egawa, Ikumi; Kawakita, Kentaro; Katagiri, Yuki; Masuda, Ami; Ishiyama, Nozomi; Yuji, Matsumoto; Li, Andrew I-kang (Universiti Teknologi MARA, Perak, 2019)
The research explains about workplace reform, aimed at improving productivity of General Affairs and Policy Planning department of Seiyo officeby changing management through the user participation workshop at 4th floor of Seiyo city office and on the changes of workplace reform. The purpose of this research is to find the changes that are worker's behaviour and worker’s awareness of workplace through workplace reform. The researchers surveyed changes, worker's behaviour and worker's awareness of workplace using workplace reform at 4th floor of Seiyo office as case study. In workplace reform, in order to create a place where new work style can be practiced, the researchers conducted the user participation workshops with workers a total of 6 times. Through the workshops, concept of work style and plan of renovation were proposed. In addition, the researchers did a survey using two methods which were a set of questionnaire and 3 observationsthat is before the workplace renovation, 3 months after the renovation, and 1 year and 3 months after the renovation. The findings obtained from the questionnaire in the first three months after the renovation showed that the opinions of the workers were divided between pros and cons against workplace reform. However, the survey of 1 year and three months after the renovation showed that almost all workers are satisfied with the new environment. In addition, the researchers found that a positive correlation exist between participation rate of workshops and the satisfaction level. The findings suggest the worth of workshops for workplace reform. In the Observation Survey, the workers needed to select a place freely where they can work comfortably after the workplace reform. For example, they chose to work in refresh space. In addition, the findings from the survey showed that the floor became livelier when the participation rate increses at that workplace. Additionally, the participants became more conscious of the work style such as features of work style, after workplace renovation; they are able to clearly differentiate between short intermittent works separated by conversation and phone and personal work on concentration.